Wokół początków kościoła pod wezwaniem Krzyża Świętego w Gnieźnie - Muraszko, Michał (Studia Europaea Gnesnensia, 2012)
The article discusses the beginnings of the holy cross church in Gniezno. among other things, it addresses the questions of the founder, the date the temple was granted to the holy sepulchre order and the characteristics of the settlement where it was erected.